1993
DOI: 10.1203/00006450-199302000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Metalloporphyrin Heme Oxygenase Inhibitors Based on Potency and Photoreactivity

Abstract: The heme oxygenase inhibitor, tin protoporphyrin, is being studied for the prevention of neonatal jaundice. This potential drug, however, is also a photosensitizer that could cause serious and unknown side effects when administered to newborns. Therefore, we have developed in vitro and in vivo procedures for the screening and further characterization of potentially safe heme oxygenase inhibitors. The ideal inhibitor: 1) contains a biocompatible metal, 2) is not degraded in tissues, 3) is a highly potent inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 21 publications
6
125
0
Order By: Relevance
“…These results confirm earlier in vitro observations describing CrMP as not photoreactive (20). Although we found no photosensitizing effects of CrMP in vivo, its safe use in neonates is concerning because of its chemical toxicity, which (25) demonstrated that 40 µmol CrMP/ kg intravenously decreases mean arterial pressure, sinusoidal diameter, and blood flow in rats.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results confirm earlier in vitro observations describing CrMP as not photoreactive (20). Although we found no photosensitizing effects of CrMP in vivo, its safe use in neonates is concerning because of its chemical toxicity, which (25) demonstrated that 40 µmol CrMP/ kg intravenously decreases mean arterial pressure, sinusoidal diameter, and blood flow in rats.…”
Section: Discussionsupporting
confidence: 80%
“…Both are potent inhibitors of HO, are orally absorbable, and have negligible effects on nitric oxide synthase and soluble guanylyl cyclase (10). Moreover, CrMP does not affect brain or spleen HO activity 24 h after oral administration (unpublished data), decreases liver HO activity in a hemolytic model (unpublished data), and is not photoreactive (20). We have shown that ZnBG is highly potent and fast-acting with a short duration of action, minimally increases HO-1 gene expression and protein levels, and decreases HO activity and bilirubin production in a hemolytic mouse model (19,21).…”
Section: Articles Schulz Et Almentioning
confidence: 86%
“…The concentration was adjusted to 1.2 mM. 18 Concentrations were then varied through appropriate dilutions with buffer. All experiments were conducted under subdued light.…”
Section: Reagentsmentioning
confidence: 99%
“…17 Natural and synthetic derivatives of heme (iron protoporphyrin) or metalloporphyrins (Mps) have been found to inhibit competitively in vitro and in vivo HO activity. 18 In vivo administration of Mps results in the suppression of plasma bilirubin, 19 total body CO excretion 20 and biliary heme excretion. 17,21 As a result, these compounds have potential use for the prevention of neonatal jaundice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation